A fit-gap analysis of the National Certificate (vocational) Information Technology and Computer Science curriculum against the needs of the South African ICT industry - Hove, Darlington (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.